Avidity of IgG antibodies against excreted/secreted antigens of Toxoplasma gondii: immunological marker for acute recent toxoplasmosis Avidez de anticorpos IgG anti-antígeno de secreção e excreção de Toxoplasma gondii: marcador imunológico de toxoplasmose aguda recente - Patrícia Regina Barboza Araújo; Antonio Walter Ferreira (Revista da Sociedade Brasileira de Medicina Tropical, 2008)
Detection of anti-toxoplasma IgM antibodies has frequently been used as a serological marker for diagnosing recently acquired toxoplasmosis. However, the persistence of these antibodies in some patients has complicated the interpretation of serological results when toxoplasmosis is suspected. The purpose of the present study was to evaluate the avidity of IgG antibodies against excreted/secreted antigens of Toxoplasma gondii by means of immunoblot, to establish a profile for acute recent infection in a single serum sample and confirm the presence of residual IgM antibodies obtained in automated assays. When we evaluated the avidity of IgG antibodies against excreted/secreted antigens of Toxoplasma gondii by means of immunoblot, we observed phase-specific reactivity, i.e. cases of acute recent toxoplasmosis presented low avidity and cases of non-acute recent toxoplasmosis presented high avidity towards the 30kDa protein fraction, which probably corresponds to the SAG-1 surface antigen. Our results suggest that the avidity of IgG antibodies against excreted/secreted antigens of Toxoplasma gondii is an important immunological marker for distinguishing between recent infections and for determining the presence of residual IgM antibodies obtained from automated assays. A detecção de anticorpos IgM antitoxoplasma tem sido freqüentemente utilizada como marcador sorológico para o diagnóstico de toxoplasmose de aquisição recente. Entretanto, a persistência destes anticorpos em alguns pacientes tem complicado a interpretação dos resultados sorológicos quando a toxoplasmose é suspeitada. A proposta deste trabalho foi avaliar a avidez de anticorpos IgG contra antígenos de secreção e excreção de Toxoplasma gondii por immunoblot, para estabelecer um perfil de infecção recente aguda em uma única amostra de soro e confirmar a presença de anticorpos IgM residuais obtidos nos testes automatizados. Quando a avidez de anticorpos IgG contra antígenos de secreção e excreção Toxoplasma gondii, por immunoblot, foi avaliada, observou-se ...